Tradition and Moderation: Exploring the Values of Religious Moderation in the Local Wisdom of the Jrahi Pati Community - Destina Marta Fiani; Dany Miftah M.Nur; Abdul Karim (JURNAL PENDIDIKAN IPS, 2024)
The focus of this research is the implementation of religious moderation in the cultural sector. The local wisdom possessed by the Jrahi people is not just a cultural symbol. However, it functions as a means of creating religious moderation. By prioritizing attitudes of tolerance, mutual cooperation and mutual respect in the practice of local wisdom, it can encourage peace and harmony in a multicultural society. Therefore, it is important to explore how local wisdom can function as a mediator in the process of religious moderation. This research aims to analyze the values of religious moderation in the local wisdom of the Jrahi Gunungwungkal Pati community. The research method used is qualitative research with field research. Then the researcher used interview and documentation techniques to collect data. Interviews were conducted both structured and unstructured with three informants, namely the Head of Jrahi Village and the Jrahi community who had an understanding of local wisdom. Meanwhile, documentation is carried out by looking for written references that can support the researcher's research. The results obtained from this research are that currently there is still some local wisdom preserved by the Jrahi community in the form of alms to the earth, barikan, nlungi cows, and dawuhan. Through this local wisdom, there are values of religious moderation that can be analyzed, such as tawassuth, tasamuh, musawah, shura', La 'unf, and I'tibar al-'urf.